A simulation-based cost-effectiveness analysis of reflex DNA versus multi-sample adolescent screening for thalassaemia in east Malaysian schools - Abd Rahim, Azrin Syahida; Mohamed, Don Ismail; Abd. Rahim, Nour El Huda (Malaysian Public Health Physicians' Association, 2025)
Summary This study compares the cost-effectiveness of two school-based thalassemia screening protocols—multi-sample (P1) and single-sample Reflex DNA (P2)—in Sabah and Sarawak using 2018 National Thalassemia Screening Programme (NTSP) data. Although P2 was 9–11% costlier upfront, it eliminated dropouts and improved carrier detection. Sabah, a high-prevalence state, demonstrated superior cost-effectiveness with P2 (RM379.95 per carrier detected) compared to Sarawak (RM821.85). Lifetime treatment cost savings for avoided births with thalassemia major were substantial. The findings support the phased implementation of P2, starting with high-prevalence states, to reduce the economic burden on Malaysia’s healthcare system.